3D‐Printed Nerve Conduits with Live Platelets for Effective Peripheral Nerve Repair. (11th August 2020) - Tao, Jie; Liu, Haofan; Wu, Wenbi; Zhang, Jiumeng; Liu, Sijia; Zhang, Jing; Huang, Yulan; Xu, Xin; He, Hongchen; Yang, Siming; Gou, Maling
Abstract: Platelets can secrete multiple growth factors for peripheral nerve repair. However, topically injected platelets are rapidly activated followed by burst release of the cargos, causing limited therapeutic efficiency in vivo. Herein, a platelet‐incorporated hydrogel conduit is shown that acts as a biosynthetic nerve conduit for peripheral nerve repair. This conduit is prepared by rapid 3D printing of the live platelets mixed with bio‐ink containing gelatin methacrylate (GelMA) and poly(ethyleneglycol)diacrylate (PEGDA). The hydrogel can significantly prolong the survival of the incorporated platelets. While the conduit provides a physical foundation for bridging the nerve gaps, live platelets in the conduit sustained‐release multiple growth factors to promote the nerve repair. The in vivo therapeutic efficiency of this platelet‐incorporated nerve conduit is tested in bridging a 10 mm gap in sciatic nerves. The results of morphological, electrophysiological, and histological assessments indicate that the incorporated platelets can significantly promote the hydrogel conduits in peripheral nerve repair. The demonstrated 3D bioprinted nerve conduit with live platelets may show potential clinical application in peripheral nerve repair. Abstract : A hydrogel nerve conduit containing live platelets is bio‐printed. This 3D‐printed conduit can provide a favorable microenvironment for the prolonged survival of the incorporated platelets and sustained release of multiple growth factors, contributing to the regeneration and functional recovery of the injured peripheral nerves. The proposed conduit shows great potential in clinical applications.